2023
DOI: 10.3390/molecules28186566
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Neuroprotective Effect of Thymoquinone on Scopolamine-Induced In Vivo Alzheimer’s Disease-like Condition: Mechanistic Insights

Hend E. Abo Mansour,
Aya Ibrahim Elberri,
Mai El-Sayed Ghoneim
et al.

Abstract: Background: Alzheimer’s disease (AD) is a common neurodegenerative disorder without effective treatment. Thymoquinone (TQ) has demonstrated potential in exhibiting anti-inflammatory, anti-cancer, and antioxidant characteristics. Despite TQ’s neuroprotection effect, there is a scarcity of information regarding its application in AD research, and its molecular trajectories remain ambiguous. Thus, the objective of the current investigation was to examine the potential beneficial effects and underlying mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…However, these effects were mitigated when mice were pretreated with DON and CTN. Previous studies have found comparable findings concerning the impacts of scopolamine [50,51] and DON [50,52].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, these effects were mitigated when mice were pretreated with DON and CTN. Previous studies have found comparable findings concerning the impacts of scopolamine [50,51] and DON [50,52].…”
Section: Discussionmentioning
confidence: 54%
“…In 0.1 M phosphate buffer (pH 7.4), a 10% (w/v) tissue homogenate was created. The homogenates (10% w/v) were then centrifuged at 10,000× g for 15 min to generate the supernatant, and the resultant cloudy supernatant liquid was used to estimate brain biochemical parameters [51].…”
Section: Collection Of Brain Samplesmentioning
confidence: 99%